SPECTRAL AND STRUCTURAL ANALYSIS FOR SODIUM SILICATE-BASED AEROGEL VIA NORMAL DRYING PRESSURE - Al-husseny, Wasan H.; Al-Sharuee, Israa F.; Ali, Ban R. (Malaysian Journal of Science, 2023)
Five types of silica aerogel were prepared at ambient pressure: sodium silicate, TEOS, and sodium silicate, with TEOS utilized as precursors. We investigated the effects of catalysis, mixing water or ethanol with the precursors, as well as the procedure of modification. Aqueous is a low-cost alternative, and many applications utilize it. A manufacturing colloidal silicic acid hydrosol was created from the ion exchange of an industrial water glass. The properties of physical, chemical, and hydrophobicity were examined via density, XRD, FTIR, and contact angle. BET, FESEM, and EDS analysis determined the structural properties. The silica hydrogel’s pore liquid (H20) was successively removed. The spectral properties confirmed the modification by the derived high contact angle of 152º, low transparency, and amorphous structure. The resulting aerogel monoliths have a well-developed mesoporous structure, a large specific surface area of 961 m2/g, and a low density of 0.04 g/cm3.